COLLABORATION OF NURSES AND DENTISTS TO IMPROVING THE ORAL HEALTH OF THE ELDERLY - Zahreni Hamzah; Nadia Kartikasari; Kushariyadi Kushariyadi (UPT Penerbitan Universitas Jember, 2023)
Background: The population aged 60 years and over will increase from year to year. Aging does not have to be followed by various diseases if assistance or treatment is done properly and correctly. Currently, dental and oral health has been established as an important risk factor that can cause disease in all body. Aims: The purpose of this article is analyzing the collaboration between dentists and nurses in the elderly community to prevent the emergence of increasingly widespread disease in the elderly. Methods: The search strategy for English and Indonesian studies relevant to the topic was carried out using the ScienceDirect, PubMed, Google Scholar, and Garuda databases limited from 2015 to 2020. The keywords used were “collaboration”, “dentist”, “elderly”, “nurse”. Full text articles were reviewed to select studies that fit the criteria. Inclusion criteria include: many factors could be collaborated in an integrated manner between dentists and nurses for the elderly in order to the elderly could maintain their health. Results: The search results obtained 21 articles. The main principles of collaboration between dentists and nurses that must be fulfilled to maintain the health of the elderly, by a holistic approach accompanied by guidelines, work procedures and management in an integrated manner, such as psychological factors, being friendly, communicating well, suggesting dental care for the elderly according to the indications (advice on the correct way of brushing teeth twice a day and periodical control, cleaning plaque-food residue, wearing dentures, removing calculus) so as not to cause more serious disturbances, digestive disorders, as well as early recognition of abnormalities that may occur in the oral cavity. Conclusions: Collaboration of nurses and dentists in the elderly community can expect to increase the knowledge of the elderly about dental and oral health, which is important to maintain their all health forever.